Poetics of Ukrainian military magic spells (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
In the article it is suggested to consider the poetics of the Ukrainian folk military spells in the context of modern development of specialist in folklore. In the article attention is focused on the scientific papers covering the problem of interpreting the term of a spell, as one of the leading minor folklore genres. Considerable attention is paid on the description of spell plot. The features of artistic creating the warrior character are traced in the texts of spells. The leading features of the semantic and functional loading of corresponding mythological characters are determined in texts of spells.
Keywords: Ukrainian folklore; spell; poetics; mental symbolics; mythological character; text; plot; tradition